Compósitos híbridos: aplicações catalíticas e oxidativas em processos ambientais - Chagas, Pricila Maria Batista (2017)
The properties of materials such as iron oxides are directly related to the dimensions and morphologies of their structure. The surface of these oxides can be modified by the combination of organic or inorganic components and are an alternative for the production of new multifunctional materials with different applications. Chitosan (Ch) is a polymer that has been widely used as a protective and stabilizing agent, which can functionalize and improve adsorbent and catalytic properties of oxides. In this study, the synthesis of chitosan-stabilized nanostructured iron oxide was carried out for application and the optimization in the aqueous Cr(VI) removal. In addition, in a continuous step to the adsorption cycle, the Ch-Fe hybrid composite, now with chromium immobilized in its structure (Ch-FeCr), was used in a second step in catalytic processes. The material was synthesized by the direct incorporation of Fe(II) into the chitosan gel, producing Ch-Fe beads. The chemical, morphological and structural characterization of the materials were performed using SEM-EDS, XRD, FTIR, TGA and DSC. The magnetic iron oxide produced together with chitosan was identified as magnetite (Fe3O4). Ch-Fe beads showed higher capacity for the removal of aqueous Cr(VI), relative to pure magnetite. The removal of Cr (VI) was pH-dependent, and the highest removal was obtained in acid medium, in which the groups present on the surface of the materials are fully protonated, facilitating the electrostatic attraction of the HCrO4 -anionic form. besides the reduction of Cr(VI) by Fe(II), in which the reduced form, Cr(III), returns to the medium and is readsorbed. Kinetic studies of adsorption showed that the adsorbed chromium follows the pseudo-second order model, indicating chemical adsorption. To describe equilibrium data, the Langmuir isothermal model best described the adsorption process. In order to maximize the Cr(VI) adsorption process, Central Composite Design (CCD) was used to evaluate how the independent parameters can interfere in the adsorption capacity of the system. The optimum conditions of the parameters (pH, chromium ion concentration, adsorbent mass and Fe(II) content in the beads) influenced the removal capacity of chromium ions, and the combination between them was important for favoring adsorption kinetics. The Ch-FeCr beads used in the degradation of methylene blue (MB) showed excellent degradation potential (93.6%). The degradation kinetics of MB was favored with the increase in temperature and the oxidant H2O2. The presence of Cr on the surface of the catalyst was responsible for the increase in catalytic activity when compared to Ch-Fe and pure magnetite. This material was also stable, without the release of the active phases of Fe or Cr, with exclusive catalysis in heterogeneous phase. In addition, Ch-FeCr beads showed catalytic stability for several consecutive reaction cycles, with technical and economical viability.